"Umoja ni ushindi (Unity is victory)": management of factionalism in the presidential nomination of Tanzania's dominant party in 2015. Issue 1 (2nd January 2018) - Tsubura, Machiko
ABSTRACT: This article examines how Tanzania's dominant party, Chama Cha Mapinduzi (CCM), managed intensified factionalism in its presidential nomination process prior to the 2015 general elections. While CCM was victorious, maintaining its long-term rule, it was seriously challenged by an opposition coalition and its presidential candidate, a former prime minister who defected from CCM after elimination from the presidential nomination. Through an analysis of CCM's presidential nominations in 1995, 2005 and 2015, the article demonstrates how a group of politicians including the former prime minister grew to be a powerful faction and created a sharp division within the party until CCM leaders eliminated him from the 2015 nomination to restore party unity in preparation for the election. Drawing on Boucek's typology of factionalism, the article argues that CCM's 2015 presidential nomination was characterised by a revival of its centralised control and the influence of retired party leaders in leadership succession to prevent a fall into degenerative factionalism that would seriously weaken the party.